Deleterious role of endothelial lectin-like oxidized low-density lipoprotein receptor-1 in ischaemia/reperfusion cerebral injury. Issue 11 (November 2019) - Akhmedov, Alexander; Bonetti, Nicole R; Reiner, Martin F; Spescha, Remo D; Amstalden, Heidi; Merlini, Mario; Gaul, Daniel S; Diaz-Cañestro, Candela; Briand-Schumacher, Sylvie; Spescha, Rebecca S; Semerano, Aurora; Giacalone, Giacomo; et al.
Lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) is implicated in cardiovascular disease by modulating apoptosis and oxidative stress. We hypothesized that LOX-1 may be involved in pathophysiology of stroke by mediating ischaemia/reperfusion (I/R)-dependent cell death. Transient middle cerebral artery occlusion (tMCAO) was performed in wild-type (WT) mice, endothelial-specific LOX-1 transgenic mice (eLOX-1TG) and WT animals treated with LOX-1 silencing RNA (siRNA). In WT mice exposed to tMCAO, LOX-1 expression and function were increased in the MCA. Compared to WT animals, eLOX-1TG mice displayed increased stroke volumes and worsened outcome after I/R. Conversely, LOX-1-silencing decreased both stroke volume and neurological impairment. Similarly, in HBMVECs, hypoxia/reoxygenation increased LOX-1 expression, while LOX-1 overexpressing cells showed increased death following hypoxia reoxygenation. Increased caspase-3 activation was observed following LOX-1 overexpression both in vivo and in vitro, thus representing a likely mediator. Finally, monocytes from ischaemic stroke patients exhibited increased LOX-1 expression which also correlated with disease severity. Our data unequivocally demonstrate a key role for LOX-1 in determining outcome following I/R brain damage. Our findings could be corroborated in human brain endothelial cells and monocytes from patients, underscoring their translational relevance and suggesting siRNA-mediated LOX-1 knockdown as a novel therapeutic strategy for stroke patients.